Collagenase digestion of bone marrow trephine biopsy specimens: an important adjunct to haematological diagnosis when marrow aspiration fails. - Maung, Z T (1993)
Failure to obtain sufficient material from marrow aspiration (dry tap) posed a diagnostic problem in two patients with pancytopenia. By using collagenase digestion of the trephine biopsy specimen, a precise diagnosis was reached. This technique is very useful because it permits flow cytometric and immunocytochemical analyses of cell suspensions obtained after collagenase digestion of the trephine biopsy specimen core. Acute leukaemia presenting with a dry tap can therefore be accurately immunophenotyped. The technique is easy to perform and merits wider use.